2010
DOI: 10.1007/s10995-010-0623-6
|View full text |Cite
|
Sign up to set email alerts
|

Are Pregnant and Postpartum Women: At Increased Risk for Violent Death? Suicide and Homicide Findings from North Carolina

Abstract: The purpose of this study is to estimate rates of suicide and homicide death among pregnant, postpartum and non-pregnant/non-postpartum women ages 14-44, and to determine comparative rates of violent death for pregnant and/or postpartum women compared to non-pregnant/non-postpartum women. North Carolina surveillance and vital statistics data from 2004 to 2006 were used to examine whether pregnant or postpartum women have higher (or lower) rates of suicide and homicide compared to other reproductive-aged women.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 40 publications
1
34
0
Order By: Relevance
“…Women in pregnancy and in the postpartum may have a high prevalence of depression and are at risk of suicide, however, the risk to die from injuries and suicide is still reported to be higher among women who are not pregnant and not in the postpartum period. 13,63 This finding is even found in settings with very good cause of death ascertainment, such as in the UK confidential enquiries, and has been attributed in part to the fact that women who become pregnant are healthier than the general population of non-pregnant women. 64 Similarly, in a demographic surveillance site in Bangladesh, violent deaths were not more common in pregnant women compared to women who were not pregnant, except for pregnant adolescents in which a higher rate to die from suicide and injuries has been observed(the higher number of injuries among pregnant adolescents has largely been explained by the high number of unwanted pregnancies in unmarried young girls).…”
Section: Discussionmentioning
confidence: 99%
“…Women in pregnancy and in the postpartum may have a high prevalence of depression and are at risk of suicide, however, the risk to die from injuries and suicide is still reported to be higher among women who are not pregnant and not in the postpartum period. 13,63 This finding is even found in settings with very good cause of death ascertainment, such as in the UK confidential enquiries, and has been attributed in part to the fact that women who become pregnant are healthier than the general population of non-pregnant women. 64 Similarly, in a demographic surveillance site in Bangladesh, violent deaths were not more common in pregnant women compared to women who were not pregnant, except for pregnant adolescents in which a higher rate to die from suicide and injuries has been observed(the higher number of injuries among pregnant adolescents has largely been explained by the high number of unwanted pregnancies in unmarried young girls).…”
Section: Discussionmentioning
confidence: 99%
“…29 This discrepancy may be due to enhanced case ascertainment since the 1990s (the PMSS data were based on death records and, in some but not all cases, linked live birth or fetal death records). Other studies on pregnancy-associated homicide have reported rates per 100,000 ranging from 8.6 in Tennessee from 1989 to 1991 (postpartum only), 6 9.3 in Maryland 1993–2008, 4 2.9 in North Carolina from 2004–2006, 30 and 2.9 in 17 states participating in the National Violent Death Reporting System (NVDRS) from 2003–2007 (SC, GA, NC, VA, NJ, MD, AK, MA, OR, CO, OK, RI, WI, CA, KT, NM, UT). 31 Although we find similar rates of pregnancy-associated homicide, Samandari et al 30 concluded that the risk of homicide was decreased among pregnant/postpartum women in North Carolina based on a homicide rate of 4.9 per 100,000 in the referent non-pregnant/non-postpartum population.…”
Section: Commentmentioning
confidence: 98%
“…[30][31][32][33][34][35][36][37][38][39][40][41] The unique physiology of pregnancy renders the patient vulnerable to hypoxemia and hemodynamic disadvantage, given the rapid development of desaturation with apnea and the presence of aortocaval compression when the patient is unconscious and supine. Therefore, all BLS interventions are essential and should be initiated rapidly and simultaneously once the rescuers arrive.…”
Section: First Respondersmentioning
confidence: 99%
“…[34][35][36][37][38] In the developed world, trauma is the leading cause of maternal mortality. Unintentional injury (primarily motor vehicle accidents), homicide, and suicide are the 3 leading components of fatal trauma.…”
Section: Trauma/suicide In Pregnancymentioning
confidence: 99%